Desenvolvimento do ARS Simulator. Seleção de comercializadores de energia - Silva , Allon Soares da; Joench, Rodrigo Luiz; Cembranel, Samuel Sandmann; Ferreira, Maria Judite Madureira Da Silva (Neutro à Terra, 2021)
This paper is a synthesis of the development of energy contracting simulator in Portugal "ARS Simulator". The simulator compares the prices of the energy traders and indicates to consumers the best option to contract energy. To make the comparison, the simulator uses trader’s data (energy prices) and the consumer’s data (energy bill, threephase or single-phase power supply and equipment's), to estimate its consumption and finally determine which trader will be the best choice.